The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1155/2022/8468438
|View full text |Cite
|
Sign up to set email alerts
|

Logistics Distribution Route Optimization Based on Genetic Algorithm

Abstract: Aiming at the problem of logistic division based on genetic algorithm, it is planned to study the improvement of logistic distribution methods. We first meet the requirements of the genetic algorithm of logistic development, use the division method to divide the delivery area of the gene, and formulate a functional delivery plan, which generally includes weight measurement, measurement time, customer value measurement, instrument measurement time, and the whole process index. We set weight goals and find the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…This current study on the application of Genetic Algorithms (GA) in logistics optimization both aligns with and diverges from previous research in several key aspects. Like the studies by Xin et al (2022) and Yang and Wu (2021), it employs GA for enhancing the efficiency and cost-effectiveness of distribution processes [11] [13]. Echoing the environmental concerns addressed in the works of Li et al (2020) and Zhang (2022), this research also emphasizes the importance of sustainable logistics, demonstrating how optimized routes can reduce carbon emissions [15] [16].…”
Section: Related Workmentioning
confidence: 98%
See 1 more Smart Citation
“…This current study on the application of Genetic Algorithms (GA) in logistics optimization both aligns with and diverges from previous research in several key aspects. Like the studies by Xin et al (2022) and Yang and Wu (2021), it employs GA for enhancing the efficiency and cost-effectiveness of distribution processes [11] [13]. Echoing the environmental concerns addressed in the works of Li et al (2020) and Zhang (2022), this research also emphasizes the importance of sustainable logistics, demonstrating how optimized routes can reduce carbon emissions [15] [16].…”
Section: Related Workmentioning
confidence: 98%
“…Recent advances in the application of Genetic Algorithms (GA) for logistics and distribution optimization are underscored by a series of studies, which highlight the efficacy and adaptability of algorithms in various logistics contexts. Xin et al (2022) focused on optimizing logistics distribution routes using GA, which showed significant time efficiency in finding optimal routes compared with traditional methods [11]. Similarly, Cui et al (2023) explored route optimization in urban logistics by introducing adaptive GA, emphasizing customer satisfaction and cost optimization, thereby validating the effectiveness of adaptive GA compared with traditional GA [12].…”
Section: Related Workmentioning
confidence: 99%
“…For the usage of a genetic algorithm, only parts of the entire supply chain can be studied at a time [55]. To overcome this problem, Xin et al [56] proposed an improved genetic algorithm to reduce the time required for local search. Meanwhile, the limitation of a genetic algorithm is that a genetic algorithm may decrease the quality and rate of convergence of the population and cause a loss of diversity in the population, which may result in premature convergence [5,57,58].…”
Section: Applications Of Genetic Algorithms In Logistics and Supply C...mentioning
confidence: 99%
“…12 GAs significantly enhance vehicle routing in transportation networks, notably reducing travel distance, fuel consumption, and CO 2 emissions. 13 Previous research has shown the effectiveness of employing GA and fuzzy logic in optimizing multimodal transportation networks. Hybrid approaches have proven successful in lowering transportation costs and enhancing service levels.…”
Section: Literature Reviewmentioning
confidence: 99%